Interaksi Sosial Pedagang Sayur di Pasar Induk Namlea Kabupaten Buru - Rusdi, M.; Loilatu, Siti Hajar; Ismail, Ismail; Mardiah, Radiatan; Papuangan, Astriani A. (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aims to describe the form of social interaction and the factors that influence the interaction carried out by vegetable sellers at the Namlea supermarket, Buru Regency. The next purpose of this research is to reveal and explain the positive values contained in social interaction. This is a descriptive qualitative research. Informants are determined by purposive sampling. Data collection was carried out in some stages such as; observation, interviews, and documentation. And data analysis is done by; data reduction, data presentation and data verification. The results of the study explain that the form of social interaction carried out by vegetable sellers at the Namlea supermarket is a form of interaction that occurs individuals to individuals, group to group and individuals to groups. This form of interaction occurs at certain times, which is divided into associative and dissociative social interactions. While the factors for the occurrence of forms of social interaction, namely; cooperation, assimilation, accommodation, competition and conflict.